Comparative Analysis of the Effectiveness of the Marine Evacuation System (MES) and Lifeboats for Passenger Evacuation in Emergency Situations on MV. Dobonsolo - Ratna Dila Vira Anzani; Iskandar Iskandar; Hartoyo Hartoyo (Applied Quantitative Analysis, 2026)
Ships are a preferred mode of transportation for Indonesian society due to their consistent focus on safety and security. In ship emergencies, the use of safety equipment such as the Marine Evacuation System (MES) and lifeboats is the primary factor in ensuring the successful evacuation of crew and passengers. However, there has been limited empirical research comparing the effectiveness of the Marine Evacuation System (MES) and lifeboats, despite the fact that delays in the evacuation process can have fatal consequences. Therefore, this study aims to analyze the comparative effectiveness of the Marine Evacuation System (MES) versus lifeboats in evacuating passengers during emergency conditions on MV. Dobonsolo. This research employs a quantitative method to compare two variables using descriptive comparative analysis techniques. The sample consists of 83 crew members from the MV. Dobonsolo. Data processing and hypothesis testing were conducted using SPSS version 26. The research results indicate that the Marine Evacuation System (MES) achieved an average effectiveness score of 4.37, while lifeboats achieved 3.89. Based on the hypothesis test results, there was a significant difference between the effectiveness of the Marine Evacuation System (MES) and lifeboats, with a two-tailed significance value of p < 0.001; therefore, Ha was accepted. The Wilcoxon signed-rank test showed that MES received higher effectiveness ratings than lifeboats, as indicated by the higher mean rank of 38.71 compared to 15.50. Therefore, it can be concluded that the MES is more effective to use than lifeboats.